Comparison of the Limited Liability Company Law in Indonesia and Brunei Darussalam - Anwar Sunarjo; Zainal Arifin Hosein (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
This study aims to compare the regulations regarding the establishment and supervision of Limited Liability Companies (LLCs) in Indonesia and Brunei Darussalam. Using a normative legal research method, this study analyzes the differences and similarities in the establishment procedures of LLCs in both countries, including legal requirements, necessary documents, and company registration mechanisms. The study also discusses the comparison in corporate supervision, including accountability, transparency, and protection for both majority and minority shareholders. The approaches used are the statute approach and the conceptual approach, focusing on the legislation governing Limited Liability Companies in both countries. The results of the study indicate that although Indonesia and Brunei Darussalam have different procedures for establishing and supervising LLCs, both countries apply the principles of accountability and transparency as the basis for shareholder protection and corporate supervision.